PERAN GURU HONORER SEBAGAI EDUPRENEUR MELALUI KEGIATAN LES PRIVAT DI MADRASAH - Anita Khusna Manzila; Riska Ariyanti; Retno Nuraini; Aisyah Rahmalia (CV. Denasya Smart Publisher, 2025)
This study aims to describe the daily activities and time management strategies employed by teachers between their main tasks and additional work. The subject was an educator at the Muhammadiyah Kauman Wiradesa Elementary School who also teaches at the Al-Qur'an Education Center and provides private tutoring. Through a qualitative descriptive approach using interviews, the findings revealed that the teacher is able to allocate time effectively through structured scheduling, so that additional activities do not interfere with their main duties. The primary motivation for undertaking additional work is not solely to increase income, but rather as a form of devotion and contribution to the welfare of others.